Keragaan Kualitas Pertumbuhan Batang Pohon Balsa (Ochroma pyramidale) Umur 1 Tahun Di KP2 INSTIPER Ungaran - Siman Suwadji; Nanda Satya Nugraha; Sri Widata (Politeknik Negeri Jember, 2026)
This study aimed to evaluate the growth performance of stem quality in 1-year-old balsa (Ochroma pyramidale) trees using the census method (100%). The research was conducted in April 2026 at the Educational and Research Forest (KP2) INSTIPER Ungaran, assessing a total population of 53 sample trees. The observed parameters included diameter at breast height (DBH), total height, clear bole height (CBH), stem straightness, number of active branches, stem taper, apical dominance, and pest/disease infestation levels. The stem quality assessment was calculated using the Stem Quality Index (SQI). The results showed an average DBH of 3.99 cm and an average total height of 283.23 cm. Based on the SQI values, the majority of the balsa trees fell into Quality Class B (Good) at 77.36%, followed by Class C (Moderate) at 9.43%, Class D (Poor) at 11.32%, and Class A (Excellent) at 1.89%. Correlation analysis among variables revealed a strong positive correlation between DBH and total height, while a negative correlation was found between the percentage of clear bole height and the total stem quality score, indicating that young trees have not yet optimally developed a stable mature canopy.